Performance improvement of variable-angle annular thermoelectric generators considering different boundary conditions. (15th January 2022) - Weng, Zebin; Liu, Furong; Zhu, Wenchao; Li, Yang; Xie, Changjun; Deng, Jian; Huang, Liang
Highlights: A new model of annular thermoelectric generator with variable-angle PN legs. Theoretical relationship of output performance between CATEG and VATEG. A 3D model of the VATEG by COMSOL to investigate the thermal stress and discuss the influence of shape difference. A 35% higher of output performance, while 30% higher of maximum thermal stress under the same volume. Abstract: Practical applications of thermoelectric generators are impeded by their low thermoelectric conversion efficiency, and improving the efficiency is vital for the advancements of thermoelectric technology. In this paper, a novel method is proposed for the performance analysis and improvement of the annular thermoelectric generators with variable-angle PN legs (VATEGs). The influence of the PN leg angle on the output performance of the VATEG is investigated by introducing an angle function. Given the volume of the PN legs, the relationship of output performance between the VATEG and traditional constant-angle ATEG (CATEG) is established under different boundary conditions based on a proposed generic model of VATEG. The results are verified numerically using the finite element method. Using the model, it is shown that the output performance of the VATEG is significantly affected by the shape of the PN leg. Finally, the thermal stress on the PN leg is next investigated using a high-fidelity 3D model of the variable-angle PN legs implemented in COMSOL, and it is found that the shape difference has a considerable influence on the thermal stability of VATEG. Under the condition of constant heat flux on the hot side and constant temperature on the cold side of the thermoelectric modules, it shows that when the radius factor is 2, the output performance can be improved by 35% with the designed VATEG, at the expense of 30% higher maximum thermal stress on the PN legs.